Allergic reactions associated with pegaspargase in adults. Issue 7 (2nd July 2016) - Chang, Abraham; Kim, Michelle; Seyer, Maggie; Patel, Samit
Abstract: One of the severe toxicities of pegaspargase (PEG) is the development of allergic reactions. This study retrospectively assessed 311 PEG doses administered to 139 acute lymphoblastic leukemia patients from May 1, 2008 to July 30, 2014 for allergic reactions based on the Common Terminology Criteria for Adverse Events (CTCAE) version 4.03. Fourteen reactions were recorded in 13 patients (9.4%). The rate of reaction did not differ between patients who received pre-medications and those who did not ( p = 0.939). Patients who received only IV PEG doses had a higher rate of reaction compared to only IM PEG (14.0% vs 1.6%; p = 0.010). Six of the seven patients with CTCAE grade 4 reactions received a majority of IV doses, suggesting that severity of reactions may increase with IV administration. Capped doses at 3750 units only had a reaction rate of 2.3%, while uncapped doses over 3750 units were found to have a 6.0% reaction rate ( p = 0.194).